FIRST DESCRIPTION OF ANTIBACTERIAL AND IN VITRO WOUND HEALING PROPERTIES OF COCOS NUCIFERA TOMENTUM - HARITHA KH; SUJITHA KUTTINATH; RAM RAMMOHAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the antibacterial, antioxidant, and in vitro wound healing property of Cocos nucifera tomentum. Methods: Ethanolic and methanolic extracts of C. nucifera tomentum were prepared using the Soxhlet extraction method and aqueous extract was prepared by the shaker flask method. These extracts were investigated for the phytochemical profile by gas chromatography and mass spectroscopy (GC-MS) and liquid chromatography-quadrupole-time-of-flight mass spectrometry (LC-Q-ToF MS), for antibacterial activity by microdilution method, for the antioxidant property by 2,2-diphenyl-1-picrylhydrazyl assay, and for in vitro wound healing activity on cell lines. Results: The preliminary phytochemical screening showed the presence of alkaloids, flavonoids, and various bioactive components. GC-MS and LC-Q-ToF MS analysis of extracts revealed the presence of bioactive compounds known to have wound healing properties as well as antioxidant and antimicrobial activities. The methanolic extract had better antibacterial activity against Proteus vulgaris and Escherichia coli, and better antioxidant and wound healing activity, when compared to the ethanolic and aqueous extracts. Conclusion: The present study suggests that C. nucifera tomentum might be a potential therapeutic source for topical antibacterial and wound healing applications.